ANALISIS KEBUTUHAN RENCANA PENGEMBANGAN DOKUMENTASI ASUHAN KEPERAWATAN ELEKTRONIK DI RUMAH SAKIT UMUM Dr. KANUJOSO DJATIWIBOWO BALIKPAPAN - , Syamsul Hadi; , dr. Lutfan Lazuardi, M.Kes., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Nursing documentation is sequence of activity which performed by nurse, started from assessment, diagnose, action plan, nursing action and evaluation, which could be transcript both in electronic and manual as well as could be accountable. Compared to the paper based, electronic documentation is faster, in time, and more clear in provide an information from the provided action. The advantage of computer utilization among others is more accurate, save the filling time, very easy in the using and the document is more quality. Paper based nursing document, had several disadvantage, such as